2004
DOI: 10.1029/2003wr002094
|View full text |Cite
|
Sign up to set email alerts
|

Temporal scaling of hydraulic head and river base flow and its implication for groundwater recharge

Abstract: [1] Spectral analyses were conducted for hourly hydraulic head (h) data observed over a 4-year period at seven monitoring wells in the Walnut Creek watershed, Iowa. The log power spectral density of the hydraulic head fluctuations versus log frequency ( f ) at all seven wells is shown to have a distinct slope or fractal dimension (D), indicating temporal scaling in the time series of water level fluctuations. The fractal dimension of the time series varies from well to well, and the spectrum for the average h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
115
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(132 citation statements)
references
References 58 publications
(69 reference statements)
13
115
2
2
Order By: Relevance
“…Most relevantly to the current study, they found that daily recharge rates at the Walnut Creek watershed may be a white noise process. The findings of Zhang and Schilling [2004] were further verified by Zhang and Li [2005] with nonstationary spectral analyses and numerical simulations. They showed that temporal scaling may indeed exist in h(t) which fluctuates as a fractional Brownian motion in most aquifers.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…Most relevantly to the current study, they found that daily recharge rates at the Walnut Creek watershed may be a white noise process. The findings of Zhang and Schilling [2004] were further verified by Zhang and Li [2005] with nonstationary spectral analyses and numerical simulations. They showed that temporal scaling may indeed exist in h(t) which fluctuates as a fractional Brownian motion in most aquifers.…”
Section: Introductionmentioning
confidence: 68%
“…For example, at our Walnut Creek site, a/S Y = 1.12 Â 10 À4 where a = 3T/L 2 [Gelhar and Wilson, 1974] and thus t 0 = 0.112 when t = 1000 days. This may explain why the Hurst coefficient calculated from the heads observed during a period of four years (1460 days) at the Walnut Creek site is 0.53 [Zhang and Schilling, 2004] (very close to 0.5) and confirm that the recharge in the Walnut Creek aquifer is a nearly white noise process with little temporal correlation. In the following numerical simulations under ECR, we will verify the theoretical results and show that the head fluctuates much more smoothly with H % 1.0 or D % 1.0.…”
Section: Nonstationary Spectral Analysesmentioning
confidence: 77%
See 3 more Smart Citations